Business communication games : photocompiable game and activities for student of English for business - Lloyd, Angela. (Oxford University Press, 1996)
The first part of the book contains 36 games which consist of one or more photocopiable worksheets. The second part contains teacher's notes giving information under the following headings: activity type, number of students, function practised, lexical area, and grammar involved, follwed by step-by-step instructions on setting up and playing the games. Finally, the index categorises the games in order to help teachers to choose a suitable game.